Financial exclusion and livelihood assets acquisition among muslim households in Ilorin, Nigeria : a structural invariance analysis. - Adewale, Abideen Adeyemi (International Islamic University Malaysia, 2014)
This study examined the relationship that exists between the latent variables of financial exclusion (credit, savings, and remittances) and sustainable livelihood assets (social capital, natural capital, physical capital, and human capital) among some poor Muslim households in Ilorin, Kwara State, Nigeria. Data elicited via survey questionnaire administered on poor Muslim households was analysed based on both factor analysis and structural equation modelling using SPSS 19.0 and Amos 19.0 software. The results indicated that the lack of financial inclusion significantly and statistically impedes the acquisition of the livelihood assets. The invariance analysis also revealed that both gender and educational attainment do not moderate the hypothesised structural model. The relatively small sample size and coverage of study area are major limitations to generalizing the findings. Nonetheless, the findings imply that financial inclusion strategies in Nigeria and perhaps in other Muslim majority areas should be located within a broader sustainable livelihood framework. This paper contributes to the literature on implication of financial exclusion from an integrated welfare analysis perspective given that access to, and uses of finance are viewed as independent rather than conjoined.